In-flight attributes and mindful passengers: Qualitative comparative analysis (QCA) of relationship quality and behavioural intentions configurations - Loureiro, S. (2016 Global Marketing Conference at Hong Kong Proceedings, 2016)
Create, develop, maintain and nurturing the passengers-airline relationships is crucial in a very competitive market in Europe. Relationship quality and behavioural intentions to fly again in the same airline carrier and recommend to others are core outcomes which may result from a favourable travel experience over time. However, the complexity and the multidimensional phenomenon lead us to develop a holistic framework, which posits that relationship quality and behavioural intentions do not depend on individual air-flight attributes and other individual demographic-psychological variables but on specific configurations of such attributes and variables. Thus, the framework of this study is investigated using qualitative comparative analysis and a sample of 304 passengers. Accordingly, the property space consists of all combinations of binary states, that is, presence or absence, of the 7 in-flight attributes (air quality, temperature, odour, noise, crew, layout and equipment/amenities), frequency of fly in an airline carrier, the type of airline carrier and demographic-psychological variables (age, gender, mindful) (that is, 212 combinations or configurations). Data from both Portuguese and non-Portuguese passengers, who have air travel experiences through Europe in both low cost carriers and legacy airlines (also called traditional or flag airlines) are used to test the hypotheses. The Lisbon airport agreed in helping to conduct the survey during October 2015. Research Question: Which configurations of in-flight attributes, demographic-psychological variables, frequency of fly in an airline carrier and type of airline carrier lead to relationship quality and behavioural intentions? The findings of the current study highlight the importance of coaligning the multiple attributes of air-flight attributes and other individual demographic-psychological variables, also including the frequency of fly in an airline carrier and type of airline carrier, for increasing relationship quality and behavioural intentions. Here the findings point out that complexity theory and QCA are useful tools for understand that simple antecedent conditions relate to an outcome condition of interest positively, negatively, and not at all, which of these three relationships occur depends on the observed complex antecedent conditions in which the simple antecedent conditions occur. Positive outcome (relationship quality or behavioural intention) is not the mirror opposite of negative outcome. By employing QCA, airline managers in Europe can identify whether and under what circumstances individual attributes and other variables will increase (or decrease) the relationship quality and behavioural intentions. QCA can also help managers uncover alternative ways for combining the attributes in order to induce behavioural intentions. Overall it is possible to see that crew and equipment & amenities, particularly for mindful passengers, emerge in several configurations as essential elements for the four outcomes: satisfaction, trust, affective commitment and behavioural intentions. For passengers not affectively committed to an airline, satisfaction plays an important role in their behavioural intention to fly again in the same airline carrier and recommend it to others. The combination of trust and affective commitment may also generate the intention to fly again in the same airline carrier and recommend it to others, particularly for mindful passengers. The findings contribute to managerial practices by providing new insights for improving the in-flight service provide and process. The findings also contribute to theoretical advancing of how passengers’ in-flight evaluations and their experience with an airline relate to their assessments of relationship quality and behavioural intentions.